(untitled) (Praxis Educativa, 2025)
The dispute between dehumanization and decolonization, as addressed by Franz Fanon in his work, gains relevance. By reviewing notions such as racism, colonization, the colonizer-colonized relationship, and dehumanization, we approach the process of imperialist neo-colonization and the geopolitical repositioning of the global North, focusing on the genocide in Palestine and the internal colonialism experienced by Indigenous peoples in Latin America. We also review Fanon’s notion of revolutionary emancipation to understand the capacity of the Zapatista peoples of Chiapas to oppose extermination, defend their territories, and build a process of autonomous development.